The Impact of Reliability on Patient Satisfaction in The Unit of Hemodialysis Hajj Hospital Jakarta - Dinnisa Haura Zhafira Hidayat; Valiant Zahirul Azmi; Liaramadanty Liaramadanty; Putri Nadira Khairani; Yuyun Umniyatun; Yona Mimanda; Mahesa Paranadipa Maikel (Jurnal Ners, 2025)
Healthcare services quality in the modern era has become a central concern for both public and private healthcare sectors. Healthcare services are evaluated based on several key dimensions including tangibility, responsiveness, reliability, assurance, and empathy. Among these dimensions, reliability plays a crucial role in ensuring that healthcare services are delivered accurately and consistently. This study intends to investigate the impact of reliability on patient satisfaction among patient satisfaction in the unit of hemodialysis at Hajj Hospital Jakarta. It is hypothesized that service reliability has a positive impact on the level of hemodialysis patient satisfaction. The study used a cross-sectional study design and a quantitative research method. All patients undergoing hemodialysis at Hajj Hospital Jakarta were included in the target population. A consecutive sampling technique was used to carry out the sampling procedure, resulting 118 participants in total. Data collection was carried out through a structured questionnaire over a one-month period. The collected data were analyzed utilizing SPSS 26 software to perform simple linear regression. The results of this study show that the impact of reliability on hemodialysis patient satisfaction at Hajj Hospital Jakarta is statistically significant and positive.